Exploring the Working Conditions in the Garments Industry: Identifying the Occupational Safety and Health (OSH) Status in the Garments Industry In Pakistan (The Journal of Cultural Perspectives, 2023)
This article investigates the current working conditions and the status of Occupational Safety and Health (OSH) standards in the garment industry of Pakistan. Due to the dearth of research conducted on exploring the working conditions in the garments industry in relation to OSH, this article contributes meaningfully to the scholarly literature. The findings of the research have inferred that the implementation of OSH is significantly lacking not only in the garment industry but also in other sectors of the country. The laborers are exploited as they are paid low wages, are bound to work in hazardous conditions neglecting OSH requirements, face harassment, and are given unsafe work environment. Many workers are forced to work overtime often without compensation, because they are required to complete the apparel orders within their assigned deadlines. Workplace conditions also hazardously affect workers' health. Moreover, labor unions have lost their centralized power to provide a platform to workers to raise voices for their rights. Considering this, we suggest that either new policies or amendments to the existing laws should be made to foster unionization since unions can ensure that workers’ rights are protected. OSH adoption at workplaces will not only improve the working conditions but will also enhance the labor productivity and consequent profitability of the businesses